KONTRIBUSI PENDIDIKAN PESANTREN BAGI PENDIDIKAN KARAKTER DI INDONESIA - Eko Eddya Supriyanto (Jurnal Pendidikan Nusantara, 2020)
Pesantren is one of the oldest Educational Institutions in Indonesia, and is a boarding school education that promotes moral and ethics which is the original attitude of the Indonesian people so that character education in boarding schools is very well maintained. Islamic boarding schools have a considerable role in efforts to educate the life of the nation which is the mandate of our constitution. The methodology in this study uses a mix method (qualitative and quantitative) focusing its attention on aspects of culture in Pesantren, the patterns of life of the santri and the behavior of santri. We focused on the location of this study in the Misbahul Huda Al-Amiriyah Kambangan Islamic Boarding School in Lebaksiu District, Tegal Regency.